Heat shock protein A4L is a potent autoantigen for testicular autoimmunity in mice. (June 2021) - Nagahori, Kenta; Hirai, Shuichi; Hatayama, Naoyuki; Kuramasu, Miyuki; Omotehara, Takuya; Kawata, Shinichi; Li, Zhonglian; Miyaso, Hidenobu; Ogawa, Yuki; Qu, Ning; Terayama, Hayato; Hayashi, Shogo; et al.
Highlights: Immunization with testicular germ cells (TGC) induces experimental autoimmune orchitis (EAO). HSPA4L, a purified TGC protein, was found to be a strong EAO inducer. HSPA4L could be a target and a useful biomarker of EAO. Abstract: Experimental autoimmune orchitis (EAO) may be used as a model to investigate immunological infertility in men. Murine EAO is induced via immunization with auto-immunogenic antigens (AIAgs) from testicular germ cells (TGCs). CD4 + T cells play a crucial role in EAO induction. However, whether AIAgs induce an immune response remains unclear. We aimed to identify self-antigens that induce EAO by screening a phage display library of random TGC peptides using IgG from EAO-induced A/J mice. Twenty TGC-specific AIAgs were detected, and G protein-coupled receptor kinase 2 interacting protein-1 (GIT1) and heat shock protein A4L (HSPA4L) were identified as candidate AIAgs that induce EAO. Immunization with GIT1 or HSPA4L, emulsified in complete Freund's adjuvant, resulted in 66 % or 100 % incidence of EAO, respectively, indicating that HSPA4L is a most potent AIAg that induces EAO in mice. These findings may expectedly help improve the diagnostic procedures and treatment of immunological infertility in men.